The Application Of Ore Characterization In The Production Of Iron Ore Pellets (Society for Mining, Metallurgy & Exploration, 2007)
Introduction The science of geometallurgy requires that ore characterization be performed holistically, that is, with consideration of ore quality on plant performance and product quality. Geometallurgy, by definition, requires knowledge of geology, mineralogy, extractive metallurgy and pyrometallurgy. Examples of the ore characterization challenges for the geometallurgist in the production of iron ore pellets from low-grade Proterozoic iron formation are presented here. Ore Characterization Ore characterization, the quantifying of mineralogy, grain size and the texture of ores, is an often overlooked tool in improving process efficiency. Some mineral related problems are not unique to the production of iron ore pellets; e.g. the problems caused by expanding clays in flotation. The negative impact of carbonate minerals in the ore on pellet productivity and pellet quality are unique. The long and complex geologic history of Precambrian iron formations contribute to modifications of grain size and the introduction of complex textures.